(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Dairy farming is an integral part of mixed crops-livestock farming systems where a farm household owns one to two dairy animals on average along with other animals like sheep and goats on a small land holding ranging from 0.25 hectare to 1.00 hectare. Improved breed of dairy cattle , developed technique to grow green silage would ensure an increase in the income of peasants, feel dignified as self-employed, and upgrade the living standard of family members, especially of women, who are always remain busy with the milch cattle day and night without getting any pecuniary benefit except a little milk at subsistence scale. Milk production in particular and its lucrative marketing in general is a key constraint to dairy development. The problems of the marketing need to be addressed if it is to realize all potential to strengthen the nutritious food chain and provide impetus to development of the agriculture sector. The promotion of market based dairy farming in the state would help in improving the means of support of small and marginal farmers Himachal Pradesh.